Guesstimate of thymoquinone diversity in Nigella sativa L. genotypes and elite varieties collected from Indian states using HPTLC technique - Ravi Y.; Vethamoni Irene P.; Saxena Shailendra N.; Velmurugan S.; Santanakrishnan V. P.; Raveendran M.; Bariya Himanshu; Harsh Mistry (Open Life Sciences, 2023)
Thymoquinone is a valuable metabolite derived from the Nigella sativa L. seeds and has a variety of therapeutic properties. Thymoquinone was estimated using n-hexane:ethyl acetate (8:2, v/v) green solvent system and computed at a wavelength of 254 nm using the high-performance thin-layer chromatography densitometry method in distinct varieties and genotypes congregated from different geographical regions. Genotype Ajmer Nigella-13 has the paramount thymoquinone content (247.60 µg/100 mg seed) followed by Ajmer Nigella 19 (244.5 µg/100 mg seed), while the lowest amount of thymoquinone was recorded in the genotype Ajmer Nigella-6 (42.88 µg/100 mg seed). The hierarchical cluster analysis found that the collected genotypes and elite varieties were classified into four broad clusters, and the identified chemotypes with elevated thymoquinone proportion were positioned in cluster D. Significant genotypic variation in thymoquinone content is available, that can be used in exploiting pharmaceutical applications of N. sativa L. as well as a breeding programme for specific metabolite improvement perspective.